Good governance: Pakistan's economic growth and worldwide governance indicators - Syed Sohaib Zubair; Mukaram Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
It is generally perceived that an Economy will experience rapid growth provided following Worldwide Governance Indicators (WGI) are in positive direction i.e. political instability is low, mechanisms for voice and accountability exists, control of corruption subsists and the rule of law prevails. The study aims at exploring relationship between aforementioned WGI indicators and economic growth (GDP) using estimates related to Pakistan, provided by World Bank. Moreover, researchers attempt to identify which of the WGI indicators under consideration contribute most towards economic growth. A quantitative research strategy has been adopted and statistical tools (Spearman's rho correlation and regression) have been used to test the hypotheses that researchers developed using available literature. The study concludes that out of the four dimensions of good governance, political stability contributes highly towards economic growth.
Keywords: 330; economic growth (GDP); good governance; worldwide governance indicators; Pakistan